Control of Electron Localization in Deuterium Molecular Ions using an Attosecond Pulse Train and a Many-Cycle Infrared Pulse - Singh, K. P.; He, F.; Ranitovic, P.; Cao, W.; De, S.; Ray, D.; Chen, S.; Thumm, U.; Becker, A.; Murnane, M. M.; Kapteyn, H. C.; Litvinyuk, I. V.; et al. (My University, 2010)
We demonstrate an experimental control of electron localization in deuterium molecular ions created and dissociated by the combined action of an attosecond pulse train and a many-cycle infrared (IR) pulse. The attosecond pulse train is synthesized using both even and odd high order harmonics of the driving IR frequency so that it can strobe the IR field once per IR cycle. An asymmetric ejection of the deuterium ions oscillates with the full IR period when the APT-IR time-delay is scanned. The observed control is due to the creation of a coherent superposition of 1s σg and 2p σu states via interference between one-photon and two-photon dissociation channels.